INVISIBLES E IGNORADOS: LA PATERNIDAD EN LA ADOLESCENCIA - Muñoz Chacón, Sergio (1999)
The article departs from the conviction that adolescent parenthood in the social ambit as well as in social institutions has been made invisible. The later as a consequence of paternalist and adult-centered visions that loads all the responsibility basically on the adolescent mother.It examines the relationship existent between masculinity and parenthood and its influence on adolescents.Finally, it studies the way adolescent men live their parenthood, especially among unprivileged sectors, and the aspects that bewilder their situation.